An assessment of different user–BS association policies for green HetNets in off-grid environments (2017)
ABSTRACT: Previous research has shown the relationship between the number of users con- nected to a cellular network base station (BS) and its energy consumption. For this reason, the study of optimal mechanisms that balance the load of users over the available BSs is a key element in the field of energy efficiency in cellular networks. The target of this paper is to propose and assess different user–BS association mechanisms to reduce grid consumption in heterogeneous cellu- lar networks powered by hybrid energy sources (grid and renewable energy). These schemes are compared with the traditional best-signal-level mechanism and evaluated via simulation by using key performance indicators related to grid consumption, number of users served, and average transmission rate per user. Our results show that the new proposed user allocation policies improve grid electricity consumption while reducing unserved users compared with the traditional association scheme.